The Current Status of Atmospheric Micro/Nanoplastics Research: Characterization, Analytical Methods, Fate, and Human Health Risk - Hsin-Chieh Kung; Chien-Hsing Wu; Nicholas Kiprotich Cheruiyot; Justus Kavita Mutuku; Bo-Wun Huang; Guo-Ping Chang-Chien (Aerosol and Air Quality Research)
Abstract Atmospheric plastic debris (microplastic and nanoplastic) research is comparatively little than in aquatic and terrestrial environments. Nonetheless, the research is important in understanding the risk and fate of these contaminants in the total environment. Generally, the research is limited by a lack of consensus on the characterization of plastic debris and the standardization of sampling and analysis protocols. These limitations make it difficult to compare results from studies. In response, criteria for defining plastic debris beyond size characterization have been proposed to include polymeric composition, solubility, physical state, shape, color, and origin. There are also emerging techniques, such as Py-GC/MS, which can measure smaller particles in the nanoscale range, and TGA-FTIR-GC/MS, which can accurately identify more polymers. The identification of microplastics and nanoplastics sources and formation processes is challenging. Since most polymers are inert, the adverse health risks include endocytosis and accumulation in the liver and spleen. However, most of the toxic effects of these contaminants are related to surface-bound compounds, including heavy metals and persistent organic pollutants. Some polymers, such as expanded polystyrene, decompose to form carcinogens. This paper offers an overview of the current knowledge on plastic debris in the atmosphere and will be useful to researchers interested in this field.